In teaching information and communication technologies efficiency of use - Nagymzhanova Каракат; Aldanysh Ақерке (Рroblems of engineering and professional education, 2023)
The article focuses on the effectiveness of the use of information and communication technologies in education. Based on the study of world scientists, the author opened the main directions and principles for the use of ICT in education